DEIXIS ANALYSIS ON SONG LYRICS IN THE ALBUM OF THE BLACK PARADE BY MY CHEMICAL ROMANCE A PRAGMATICS STUDY - Evi Murti Wardhani; Latifah Eka Febiyanti (Frasa)
This study focuse on a deixis analysis of theÂ  lyrics of My Chemical Romance's album "The Black Parade," especially "Welcome to the Black Parade"Â  and "Famous Last Wordsâ€ songs. The study identifies three types of deixis namely,Â  personal, temporal, and spatial. It is a descriptive qualitative studyÂ  to observe diectic expressionns then Yuleâ€™s theory about diexis is used to analyze the data. ResultÂ  shows that the most frequentÂ  deixis used is personal after that spatial and temporal. By a detail analysis in Yule's theory, this study indicates how strategic is deixisÂ  in song lyrics. It is able to convey the listeners complex narrative and emotional levels in enhancing the listener's interpretive experience. The pragmatic approach here enlights the deixis competence importance, when the listeners have limited lyricsÂ  understanding to meet the context and reference inside songs lyric. Â